Mesh-supported metal-organic framework thin films: fabrication and applications - Yap, Min Hui (2019)
Among one of the fastest growing field of materials research, metal-organic frameworks (MOFs) have been demonstrating potentially high commercial value with proposed applications in the field of energy (such as solar energy conversion and electrical energy storage) [1], environmental sustainability (including gas storage and harmful gas removal)[2], and innovative healthcare (drug delivery)[3]. This research study aim to contribute to the understanding of synthesis and applications of mesh-supported MOF thin films. To begin with, three types of MOF powder, namely: Cu3(BTC)2, Ni3(BTC)2, and Co3(BTC)2 were successfully synthesized using an optimized solvothermal growth method.Further research progress were made by depositing various thickness of Cu3(BTC)2 and Ni3(BTC)2 MOF thin films on copper and nickel substrates.After process optimizations, the most homogeneous coating with the highest 82 % product yield was achieved by depositing Cu3(BTC)2 thin film on copper mesh (sample denoted as Cu3(BTC)2@Cu). Subsequently, Cu3(BTC)2@Cu was used as precursor to prepare porous Cu/C@Cu through a direct pyrolytic decomposition process. The effects of different heating parameters on the morphology, textural properties, and electrochemical properties of the as synthesized Cu/C@Cu were studied. Besides that, Cu3(BTC)2@Cu was also used as binder-free electrodes for the preparation of prototype supercapacitors (pseudocapacitors) and hybrid lithium ion batteries. In order to evaluate the performance of Cu3(BTC)2@Cu as negatrode in supercapacitors, varies carbon material such as graphene nanoplatelet, carbon blanket, and highly electrically conductive carbon (HEC) electrodes were used as pairing material. The best performing supercapacitor device was achieved with the combination of Cu3(BTC)2@Cu negatrode and HEC positrode, with a reported energy density of 1080 µWh/cm2 and a power density of 17.9 mW/cm2. Overall, Cu3(BTC)2@Cu is a flexible material which could be applied into many applications after proper tuning of its properties. This facile preparation method is transferable and could be applied into fabricating other supported-MOF thin films and MOF-derived porous nanostructures.